Halal cosmetics and behavior of Muslim women in Indonesia: the study of antecedents and consequences - Frideswidi Aufi; Hendy Mustiko Aji (Faculty of Business & Economics, Universitas Islam Indonesia, 2021)
Purpose: This study aims to analyze the antecedents and consequences of the attitudes of Muslim women towards purchase intention of halal cosmetics. Methodology: This sample was taken by using the purposive sampling technique. In total, 232 Muslim women respondents are aware of halal-labeled cosmetics. Data is processed using Partial Least Square-Structural Equation Modeling (PLS-SEM) method with SmartPLS.Findings: The results of this study indicate that religiosity has a positive and significant influence on attitudes towards halal cosmetics, knowledge has a positive and significant influence on attitudes towards halal cosmetics, subjective norms have a positive and significant influence on attitudes towards halal cosmetics, and attitudes towards halal cosmetics has a positive and significant influence on purchase intention of halal cosmetics.Originality: Due to the inconsistent findings from past studies, the results of this study are expected to contribute to the literature in evaluating the behavioral intentions of Muslim women in Indonesia towards halal cosmetics. Cosmetics brand manufacturers can also use the results of this study for the halal labeling process of their products.